2005
DOI: 10.1002/rra.859
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Abaeté River on the reproductive success of the neotropical migratory teleostProchilodus argenteus in the São Francisco River, downstream from the Três Marias Dam, southeastern Brazil

Abstract: The curimatã-pacu Prochilodus argenteus is an important characiform from the São Francisco River basin that performs longdistance migrations for spawning upstream during the rainy season, when the temperature and photoperiod are elevated. Despite the interruption of the migratory routes by the Três Marias Dam and accentuated decline in fishing, the curimatã-pacu still sustains the fisheries at the Três Marias region in recent decades. The objective of this study was to evaluate the reproductive activity of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 29 publications
8
53
0
1
Order By: Relevance
“…This behavior is fundamental, since it can assure the reproduction and the perpetuation of populations even in situations in which principal migration routes are lost. Some recent studies have supported this trend, and reported that Prochilodus argenteus can successfully use tributaries downstream from Três Marias Dam (São Francisco River basin) for spawning (Sato et al, 2005;Godinho & Kynard, 2006). In addition, Godinho & Kynard (2006) also report the existence of different populations living in a short river stretch (~50km), using distinct migratory routes for spawning.…”
Section: Discussionmentioning
confidence: 83%
“…This behavior is fundamental, since it can assure the reproduction and the perpetuation of populations even in situations in which principal migration routes are lost. Some recent studies have supported this trend, and reported that Prochilodus argenteus can successfully use tributaries downstream from Três Marias Dam (São Francisco River basin) for spawning (Sato et al, 2005;Godinho & Kynard, 2006). In addition, Godinho & Kynard (2006) also report the existence of different populations living in a short river stretch (~50km), using distinct migratory routes for spawning.…”
Section: Discussionmentioning
confidence: 83%
“…In fact, the existence of a single panmictic population for each species associated with the highly migratory behavior support the hypothesis of extensive gene flow among shoals. The convergence between rio São Francisco and rio Abaeté is considered the most important spawning site of Prochilodus argenteus (Godinho & Kynard, 2006), mainly because of the limnological conditions offered by the junction of the two rivers, such as water flow above 600 m³/ s, water temperature over 24ºC and concentrations of dissolved oxygen above 5 mg/l (Sato et al, 2005). As suggested by Hatanaka & Galetti (2003), one fraction completes its migration toward the dam during the reproductive period, and the majority possibly migrates to locations with environmental conditions more favorable for reproduction.…”
Section: Migratory Routesmentioning
confidence: 99%
“…As suggested by Hatanaka & Galetti (2003), one fraction completes its migration toward the dam during the reproductive period, and the majority possibly migrates to locations with environmental conditions more favorable for reproduction. Sato et al (2005) (Sato et al, 2005).…”
Section: Migratory Routesmentioning
confidence: 99%
“…Changes in environmental conditions downstream from dams may negatively affect fish populations and their reproduction (Lessard & Hayes 2003, Sato et al 2005, mainly due to the de crease in temperature, which may cause a delay in spawning and embryo development and, hence, a reduction in the distribution of a species (Arantes et al 2010, Olden & Naiman 2010. The effects on fish populations downstream are not always negative.…”
Section: Introductionmentioning
confidence: 99%